2018
DOI: 10.1186/s13071-018-3054-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal parasites, with emphasis on the molecular epidemiology of Giardia duodenalis and Blastocystis sp., in the Paranaguá Bay, Brazil: a community survey

Abstract: BackgroundIntestinal protozoan parasites are major contributors to the global burden of gastrointestinal disease causing significant socioeconomic consequences. Children living in resource-poor settings with restricted access to water and sanitary services are particularly at risk of these infections.MethodsA prospective, community-based, cross-sectional survey was conducted in Paraná (southern Brazil) between May 2015 and May 2016. A total of 766 stool samples were individually collected from volunteers (male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
58
5
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 86 publications
12
58
5
9
Order By: Relevance
“…The occurrence of assemblages A and B is not surprising considering that to date, these groups have been frequently found in humans and animals infections worldwide 1,34 . The predominance of assemblage A corroborates the results of other studies in Brazil 6,25,35 , Malaysia 36 , Ethiopia 37 and Slovakia 20 . In contrast, a higher prevalence of assemblage B has been reported in children in Brazil 8,38 and in other countries 39,40 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The occurrence of assemblages A and B is not surprising considering that to date, these groups have been frequently found in humans and animals infections worldwide 1,34 . The predominance of assemblage A corroborates the results of other studies in Brazil 6,25,35 , Malaysia 36 , Ethiopia 37 and Slovakia 20 . In contrast, a higher prevalence of assemblage B has been reported in children in Brazil 8,38 and in other countries 39,40 .…”
Section: Discussionsupporting
confidence: 90%
“…This frequency was lower than those recently reported in daycare and preschool children living in communities of São Paulo State, some of them placed in regions near the study area 8,16,17 . Recently, the examination of one fecal sample has revealed Giardia infection rates ranging from 2.7% to 11% in children of preschool age in some surveys worldwide [18][19][20][21] , including Brazil [22][23][24][25] . Even when the diagnosis is based on the examination of three stool samples, the studies did not report much higher prevalence rates 8,9,16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Among these isolates, five of them identified in herring and saithe exhibited 100% sequence identity with each other and were classified as ST8. Indeed, the SSU rDNA sequence of these isolates exhibited 100% identity with those of several ST8 isolates identified from humans and animal hosts in different countries [16,33,34]. As reported in a recent epidemiological survey conducted in zoos and compiling available data from the literature [16], ST8 has been almost exclusively identified in non-human primates, to a lesser extent in marsupials and episodically in human beings in relation to a likely zoonotic transmission [16].…”
Section: St Distribution Of Blastocystis Sp In Edible Marine Fishmentioning
confidence: 64%
“…(28,2%), Endolimax nana (14,9%), and Giardia duodenalis (11%) with similar frequencies as reported in this study. It is important to add that guard association with rotavirus and cryptosporidium is frequent [ 32 ]. The presence of Dipylidium caninum (12%) found in this study in dogs has been previously reported as a zoonosis in children [ 33 ], but no cases associated with the child population were found in these communities.…”
Section: Discussionmentioning
confidence: 99%